2014
DOI: 10.1002/nbm.3172
|View full text |Cite
|
Sign up to set email alerts
|

Correlative assessment of tumor microcirculation using contrast‐enhanced perfusion MRI and intravoxel incoherent motion diffusion‐weighted MRI: is there a link between them?

Abstract: The purpose of this study was to correlate intravoxel incoherent motion (IVIM) imaging with classical perfusion-weighted MRI metrics in human gliomas. Parametric images for slow diffusion coefficient (D), fast diffusion coefficient (D*), and fractional perfusion-related volume (f) in patients with high-grade gliomas were generated. Maps of Fp (plasma flow), vp (vascular plasma volume), PS (permeability surface-area product), ve (extravascular, extracellular volume), E (extraction ratio), ke (influx ratio into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 42 publications
7
42
0
Order By: Relevance
“…In the liver perfusion parameters from IVIM do not correlate with those from model-free DCE-MRI (12). Additionally, Bisdas et al (11) also reported no evident correlation between perfusion parameters from IVIM and DSC- or DCE-MRI in patients with cerebral glioma. Our current results are very similar to these results, emphasizing no significant correlation between perfusion parameters from IVIM and DCE-MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the liver perfusion parameters from IVIM do not correlate with those from model-free DCE-MRI (12). Additionally, Bisdas et al (11) also reported no evident correlation between perfusion parameters from IVIM and DSC- or DCE-MRI in patients with cerebral glioma. Our current results are very similar to these results, emphasizing no significant correlation between perfusion parameters from IVIM and DCE-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the perfusion parameters from IVIM could be surrogate markers to the established perfusion markers from perfusion MRI in tumor imaging is unclear (1112131415222324). In terms of the head and neck, several studies have investigated the correlation between IVIM and DCE-MRI parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 D* is dependent on both blood velocity and mean capillary segment length, 13 which are heterogeneous in the tortuous tumor vasculature. Indeed, we observed poor repeatability for D* in HCC lesions, which is consistent with recent studies on repeatability of IVIM-DWI metrics in liver and HCC 18 and in liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The fast ADC-bi values of the tumor and the normal rectal wall were much bigger than fast ADC-mono values of both, which showed that the IVIM-bi model may overestimate the proportion of perfusion in water diffusivity. Moreover, some studies21242526 found that there was no or weak correlation between fast-ADC and CBF, f value and CBV, which meant that fast-ADC and f value might not represent the true perfusion in the tumor. The AUC of fast-ADC was smaller than that of slow-ADC, which demonstrated the lower diagnostic efficiency of fast-ADC in the discriminating malignant lesions and normal tissue.…”
Section: Discussionmentioning
confidence: 99%